2020
DOI: 10.1016/j.jneuroim.2020.577269
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NFƙB and MAPK signaling pathways in the preventive effects of Ganoderma lucidum on the inflammation of BV-2 microglial cells induced by LPS

Abstract: Ganoderma lucidum extract (GLE) is a potent ancient Asian remedy for the treatment of various diseases. This study investigated GLE preventive effects on LPS-stimulated inflammation of BV-2 microglial cells. The results show that pre-treatment with GLE decreased expression of pro-inflammatory cytokines: G-CSF, IL1-α, MCP-5, MIP3α, and, with a higher effect in MIP3α. In RT-PCR assays, pre-treatment with GLE decreased mRNA expression of CHUK , NFκB1/p150 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…The NF-ĸB response is different at different stages of disease progression in AD; it is involved in the development of plaque and during the signaling of cytokine and inflammation during disease progression. Slowing down the activity of NF-ĸB results in decreased progression of the disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NF-ĸB response is different at different stages of disease progression in AD; it is involved in the development of plaque and during the signaling of cytokine and inflammation during disease progression. Slowing down the activity of NF-ĸB results in decreased progression of the disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the concentration increased, the expression of phospho-p65 was inhibited. Moreover, the GL extract also had a inhibitory effect on the activation of MAPK, including p38, JNK, and ERK [ 34 ]. We observed that the heat-dried GL extract had a significantly higher inhibitory effect on NF-κB and MAPK signaling compared to the freeze-dried GL extract, indicating that the inhibitory effect of the GL extract is dependent on the postharvest treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above in vitro studies, it can be assumed that GLP may act in early stages Alzheimer’s disease to reduce inflammation. In a similar study, the effect of G. lucidum fruiting body extract (GLE), which contained a large polysaccharide fraction, was tested on BV2 cell line [ 63 ]. GLE decline the level of pro-inflammatory cytokines in cells by modulating the signaling pathways of NF-ĸB and MAP kinases that regulate the synthesis of proteins involved in inflammatory processes [ 63 ].…”
Section: Bioactivity Of Polysaccharides From Ganoderma Lucidummentioning
confidence: 99%
“…In a similar study, the effect of G. lucidum fruiting body extract (GLE), which contained a large polysaccharide fraction, was tested on BV2 cell line [ 63 ]. GLE decline the level of pro-inflammatory cytokines in cells by modulating the signaling pathways of NF-ĸB and MAP kinases that regulate the synthesis of proteins involved in inflammatory processes [ 63 ]. It is therefore highly probable that G. lucidum fruiting body extract can also play a role in the prevention of neurodegenerative diseases by modulating signaling pathways.…”
Section: Bioactivity Of Polysaccharides From Ganoderma Lucidummentioning
confidence: 99%